A microeconometric analysis of the springboard subsidiary: The case of Spanish firms - Carolina Caicedo Marulanda; Jhon James Mora Rodríguez; José Bla Barber; Fidel León Darder (Kiel Institute for the World Economy (IfW), 2015)
This article provides a microeconometric analysis of the distinctive characteristics of springboard subsidiaries that have a positive impact on the subsidiaries' performance. Based on panel data estimations for subsidiaries of European multinational companies with a presence in Spain, the authors found that if the subsidiary located in the springboard country is a springboard subsidiary, its performance increases by 3.6%. When the subsidiary has a technological relationship with another subsidiary, its performance increases by 1.9%. If the subsidiary that has the technological relationship is a springboard subsidiary located in a springboard country, this increases performance by 1.8%. Growth of 1% in absorption capacity increases a subsidiary's performance by 1.2%. Finally, low autonomy reduces the performance of a subsidiary by 34.4% compared to independent subsidiaries or those with a high degree of autonomy.
Keywords: C23; D22; 330; Microeconometric Analysis; Springboard Country; Springboard Subsidiary; Subsidiary - Specific Advantage; Firms Performance; Panel Data